UNPACKING THE EFFECTS OF FINANCIAL INCLUSION ON BANK EFFICIENCY: A CROSS-COUNTRY ANALYSIS OF THE ASEAN 5+1 BANKING SECTORS - Shukur, Nabilah Abdul; Sufian, Fadzlan (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
The impact of financial inclusion on the well-being of economic development and the stability of the financial system has been widely documented in previous literature. However, the empirical evidence of the financial inclusion effect on bank efficiency remains unclear. It seems surprising because when a country is financially exclusive, it can dampen economic growth, thus inhibiting inclusion, especially for the unbanked population in ASEAN 5+1 countries. This paper investigates the relationship between financial inclusion and bank efficiency within the ASEAN 5+1 banking sectors, focusing on the country’s income levels. For this purpose, a dataset of 1,500 observations spanning from 2013 to 2021 was used. We utilize Data Envelopment Analysis (DEA) and Ordinary Least Squares (OLS) regressions to analyse the relationship between financial inclusion indicators and bank efficiency. Our empirical findings reveal that the pattern varies across countries with different income levels. This study suggests that financial inclusion in high- and middle-income countries positively affects bank efficiency, while in low-income countries, it unfavourably influences bank efficiency. This implies the need to draw attention to the side effects of bank inefficiency on increasing financial inclusion and achieving inclusion goals.